2010
DOI: 10.2165/11584790-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Older Womenʼs Views about Prescription Osteoporosis Medication

Abstract: Older women with osteoporosis need clear information about their condition, including the diagnosis, the implications of the diagnosis, treatment options, medication effectiveness and side effects. Physicians should check with their patients to confirm understanding and address concerns, as older women may not always voice their reservations and concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 16 publications
1
67
0
Order By: Relevance
“…18 More general descriptions of medicines as effective tools to care for oneself beyond what can be obtained with diet and exercise are shared in interviews with patients suffering from heart failure and osteoporosis. 25,27 In terms of expressing expectations, it has been suggested that this is predominantly done by patients looking for specific outcomes, especially in relation to a condition that greatly impacts on their daily lives. Context Semi-structured interviews with 61 patients recruited from GP practices in three areas in the UK.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…18 More general descriptions of medicines as effective tools to care for oneself beyond what can be obtained with diet and exercise are shared in interviews with patients suffering from heart failure and osteoporosis. 25,27 In terms of expressing expectations, it has been suggested that this is predominantly done by patients looking for specific outcomes, especially in relation to a condition that greatly impacts on their daily lives. Context Semi-structured interviews with 61 patients recruited from GP practices in three areas in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Confirmation of effects is sought, and lack of identifiable effects can lead to the medicine being seen as not useful 10,24,26,27 Medicines offer something beyond what is achieved by diet and exercise 25,28 A medicine prescribed for prevention 'stops a heart attack', 'cures the bones' or 'does the job the doctor says need to be done'…”
Section: Experiences and Evaluation Develop Over Timementioning
confidence: 99%
See 3 more Smart Citations